To question about corporate spores and their jurisdiction - Бутрин, Н. С. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article is devoted to the legal analysis of the subdepartment of corporate disputes. A short theoreticalreview determination of concept «corporate rights» is done, alluding to the current legislation of Ukraine.Also is given attention to the separate types of corporate disputes.